Efektivitas Program Kartu Prakerja Dalam Meningkatkan Kesejahteraan Penerima Pada Kecamatan Sampung Ponorogo Ditinjau Perspektif Ekonomi Islam - Anik Nur Ria; Candra Febrilyantri (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: Effectiveness is a measure that shows the extent to which an objective in terms of quantity, quality and time has been achieved in management, as well as what goals have been achieved to create creativity. The existence of a pre-employment card program for job seekers, people who have lost their jobs, as well as for people who want to improve their skills to meet their daily needs is very important to improve people's welfare. The main objective of this study was to analyze the implementation of the pre-employment card program in Sampung District, and to analyze the strategy of the pre-employment card program in the selection process in Sampung District, to analyze the effectiveness of the pre- employment card program in improving people's welfare in Sampung District. Research Methods: This research method uses a qualitative approach and this type of research uses a type of field research. Collecting data using interviews, observation, and documentation. Techniques in data analysis using data collection, data reduction, data presentation, and drawing conclusions. Results: Based on the results of field research, the authors concluded: 1) The enthusiasm for the implementation of the pre-employment card program in Sampung District was very high, both for the local government and its residents. 2) The strategy adopted is to present an IT team in each village and disseminate this information on social media. 3) The welfare of the community itself has not been fully fulfilled, but from the incentives obtained for additional business capital for daily needs, so that related to the welfare of the Islamic perspective has been fulfilled due to an increase in the economic level, and related to skills welfare is also fulfilled where there is training.